2012
DOI: 10.1099/ijs.0.040287-0
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the status of Streptomyces setonii and reclassification of Streptomyces fimicarius as a later synonym of Streptomyces setonii and Streptomyces albovinaceus as a later synonym of Streptomyces globisporus

Abstract: The 16S rRNA and gyrB genes of 22 Streptomyces strains belonging to the Streptomyces griseus cluster were sequenced, and their taxonomic positions were re-evaluated. For correct analysis, all of the publicly available sequences of the species were collected and compared with those obtained in this study. Species for which no consensus se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…For example, S. griseus and Streptomyces setonii were once considered to be the same species [5, 6] but later they were validly recognized as independent species again [7]. DNA–DNA relatedness is currently used as the ultimate means to define bacterial species [8, 9].…”
Section: Full-textmentioning
confidence: 99%
“…For example, S. griseus and Streptomyces setonii were once considered to be the same species [5, 6] but later they were validly recognized as independent species again [7]. DNA–DNA relatedness is currently used as the ultimate means to define bacterial species [8, 9].…”
Section: Full-textmentioning
confidence: 99%
“…The maximum-likelihood phylogenetic tree generated based on the strain’s core proteomes showed that the closest relatives of the MW-W600-10 strain are S. fimicarius NRRL ISP-5322 and S. baarnensis NRRL B-2842 ( Figure 1 ). Importantly, the phylogeny of the S. fimicarius NRRL ISP-5322 strain was revised recently, and it was suggested that the strain should be classified as S. setonii [ 51 ]. Here, we kept the taxonomical name of the NRRL ISP-5233 strain displayed in the NCBI database.…”
Section: Resultsmentioning
confidence: 99%
“…Four isolates (NNPR52, NNPR62, PWS6 and PWS52) had less than 98% similarity to its nearest known strain, which suggested that these isolates could be novel taxa [ 30 ] This is supported by the description of various phylogenetically similar (> 99%) Streptomyces strains as new and novel species [ 43 45 ]. Intragenomic heterogeneity, intraspecific disparity, inadequate resolution capacity and inconsistent DNA–DNA relatedness limit species-level delineation by 16S rRNA gene sequence data within the genus Streptomyces [ 46 48 ]. In fact, a definitive 16S rRNA gene sequence similarity threshold cannot be defined to describe whether an actinobacterium belonging to Streptomyces may or may not be a novel species [ 49 ].…”
Section: Discussionmentioning
confidence: 99%